The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1080/03768350902899595
|View full text |Cite
|
Sign up to set email alerts
|

Economic decline and gentrification in a small town: the business sector in Aberdeen, Eastern Cape

Abstract: Small towns are a neglected topic of study but they are gaining importance in South Africa because of rapid urbanisation. This paper discusses a case study of business development and gentrification in Aberdeen, a small town in the Eastern Cape's Karoo. Although there has been a long-term decline in Aberdeen's economy, major changes are now taking place that call for more focused development policies. The findings of a 2006 business survey in Aberdeen are presented here and integrated with findings from the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…What Webster describes is well borne-out by a study of the business sector in Aberdeen (Atkinson 2009), and is equally applicable to any number of small Karoo towns. One indication of this is the number of 'emerging' small building contractors -mainly from the local black and coloured communities-that Atkinson reports have sprung up to take advantage of the new opportunities created by the wave of gentrification (see also Hoogendoorn et al 2009: 79-80).…”
Section: Under the Radar Screenmentioning
confidence: 96%
See 2 more Smart Citations
“…What Webster describes is well borne-out by a study of the business sector in Aberdeen (Atkinson 2009), and is equally applicable to any number of small Karoo towns. One indication of this is the number of 'emerging' small building contractors -mainly from the local black and coloured communities-that Atkinson reports have sprung up to take advantage of the new opportunities created by the wave of gentrification (see also Hoogendoorn et al 2009: 79-80).…”
Section: Under the Radar Screenmentioning
confidence: 96%
“…To some degree then, at least where rather more affluent individuals are concerned, answers to the questions raised by Visser are in the process of revealing themselves in the form of a new social movement characterised by counterurbanisation in favour of the platteland (Atkinson 2009). This is radically revising general perceptions of the Karoo-a region which was once almost universally regarded as a desolate wasteland fit for nothing but sheep (Dobson and Mowszowski 2004;Nel and Hill 2008;Wright 1929: 135).…”
Section: Under the Radar Screenmentioning
confidence: 97%
See 1 more Smart Citation
“…In the process, rural gentrification has 'benefited' some towns (Atkinson 2009, Donaldson 2009) while others have remained unpopular for revival. Activities and functions which were (in certain cases, exclusively) part of the metropolitan domain can also be found in the nonmetropolitan sphere.…”
Section: Investing In the Creative Classmentioning
confidence: 98%
“…Vranitzky (1995) noted that public investments should contribute to decreasing people's tendency to emigrate by increasing economic welfare. It can also be observed that public investment increasing the quality of infrastructure contributes to a trend towards 'reverse migration' or 'population turnaround' as a result of the renewed preference for rural living (Atkinson, 2009;Brown and Wardwell, 1980). The tendency of communes to invest is connected with expanding fixed material resources, and is therefore a benefit to the local community.…”
Section: Significance Of Local Government Investment For Local Develomentioning
confidence: 99%